2020
DOI: 10.31234/osf.io/9c57t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Which facial features are central in impression formation?

Abstract: Which facial characteristics do people rely on when forming personality impressions from faces? Previous research has uncovered an array of facial features that influence people’s impressions. Even though some (classes of) features, such as facial width-to-height ratio or resemblances to emotional expressions, play a central role in theories of social perception, their relative importance in impression formation remains unclear. Here, we model faces along a wide range of theoretically important dimensions. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In contrast, these individuals are seen as less intelligent than the average person (Deska et al, 2018b). However, recent findings suggest that the impact of fWHR on dispositional inferences might be smaller and less reliable than previously thought, particularly when considering male faces (see Durkee and Ayers, 2021;Jaeger and Jones, 2020). Thus, the contribution of fWHR to person perception is still a matter of debate.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, these individuals are seen as less intelligent than the average person (Deska et al, 2018b). However, recent findings suggest that the impact of fWHR on dispositional inferences might be smaller and less reliable than previously thought, particularly when considering male faces (see Durkee and Ayers, 2021;Jaeger and Jones, 2020). Thus, the contribution of fWHR to person perception is still a matter of debate.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, several recent studies have demonstrated that physical characteristics that have shown clear and robust effects on social judgements of faces in studies using this method are relatively poor predictors of social judgements when the physical characteristics and ratings are taken from natural (i.e. unmanipulated) face images that vary simultaneously on multiple dimensions (Holzleitner et al, 2019;Jaeger & Jones, 2022;Lee et al, 2021;Said & Todorov, 2011).…”
mentioning
confidence: 99%
“…The mostly commonly used approach is bootstrapped regressions, in which only those components that predict the outcome variable consistently across iterations are retained (Holzleitner et al, 2019;Said & Todorov, 2011). An alternative but less widely used approach is to employ regularized regressions (Jaeger & Jones, 2022), which shrink uninformative predictors to small values, retaining informative ones. These are most naturally approached from a Bayesian perspective (Jones & Kramer, 2021), within which prior distributions put very low probability on large estimates, which can be overcome only with strong data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the question of learning how much one likes the attribute Reditry is not the same as learning what facial features cause a face to be high or low in Reditry. Our study is focused on the former evaluative process; the latter attributional process is fascinating, too (and better studied; seeJaeger & Jones, 2020;Zebrowitz & Montepare, 2008), but it was not the focus of the current investigation.…”
mentioning
confidence: 99%